Bacterial cellulose composites: Synthetic strategies and multiple applications in bio‐medical and electro‐conductive fields. Issue 12 (23rd September 2015) - Ul‐Islam, Mazhar; Khan, Shaukat; Ullah, Muhammad Wajid; Park, Joong Kon
Abstract: Bacterial cellulose (BC), owing to its pure nature and impressive physicochemical properties, including high mechanical strength, crystallinity, porous fibrous structure, and liquid absorbing capabilities, has emerged as an advanced biomaterial. To match the market demand and economic values, BC has been produced through a number of synthetic routes, leading to slightly different structural features and physical appearance. Chemical nature, porous geometry, and 3D fibrous structure of BC make it an ideal material for composites synthesis that successfully overcome certain deficiencies of pure BC. In this review, we have focused various strategies developed for synthesizing BC and BC composites. Reinforcement materials including nanoparticles and polymers have enhanced the antimicrobial, conducting, magnetic, biocompatible, and mechanical properties of BC. Both pure BC and its composites have shown impressive applications in medical fields and in the development of optoelectronic devices. Herein, we have given a special attention to discuss its applications in the medical and electronic fields. In conclusion, BC and BC composites have realistic potential to be used in future development of medical devices, artificial organs and electronic and conducting materials. The contents discussed herein will provide an eye‐catching theme to the researchers concerned with practical applications of BC and BC composites. Abstract : The structural features of pure bacterial cellulose (BC) advocate synthesis of composites with diverse range of materials including nanomaterials and polymers. The composites overcome numerous limitation of pure BC and bless it with additional features. BC composites materials are utilized for multiple applications including development of biomedical devices, wound healing, facial masks and formation of opteoelectronic devices.This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visit www.afob.org.